Ritual Nyadiri Sebagai Etnopedagogi Spiritual Hindu Kaharingan Dalam Pembelajaran Nilai - Megawati Megawati; Kunti Ayu Vedanti; Yoppie Yoppie (Jayapangus Press, 2026)
Value education in contemporary society faces serious challenges due to the dominance of cognitive-oriented and instrumental educational approaches that are often detached from local cultural and spiritual contexts. As a result, character formation, moral awareness, and the cultivation of meaningful life values tend to be insufficiently internalized. Within the Hindu Kaharingan community, religious rituals continue to function as practical spaces for value formation, particularly through the Nyadiri ritual, which has commonly been perceived as a ceremonial practice rather than a pedagogical medium. This study aims to analyze the Nyadiri ritual as a form of Hindu Kaharingan spiritual ethnopedagogy and to explain its role in value learning. This study employs a qualitative descriptive approach grounded in a spiritual ethnopedagogical framework. Data were obtained through literature review, documentation of the Nyadiri ritual, and cultural narratives that reflect the Hindu Kaharingan community’s understanding of ritual meanings. Data analysis was conducted qualitatively through symbolic interpretation and reflective analysis to reveal the pedagogical dimensions embedded in the ritual. The findings indicate that the Nyadiri ritual embodies a systematic pedagogical structure despite not being formalized within institutional education. Spiritual, moral, and social values are transmitted through direct experience, ritual symbols, and collective participation across generations. The ritual functions as an experiential learning space that enables reflective and sustainable internalization of values. Its structure demonstrates an integration of spiritual awareness, moral habituation, and social solidarity that contributes to the formation of ethical consciousness and character. The study concludes that the Nyadiri ritual can be positioned as a model of spiritual ethnopedagogy that is relevant to the development of contextual, holistic, and sustainable value education. These findings highlight the strategic potential of local wisdom and religious ritual practices as meaningful resources for responding to contemporary educational challenges.